2015
DOI: 10.18533/ijbsr.v5i12.896
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and Job Burnout: Does Religious Coping Moderate the Relationship?

Abstract: This study aimed at investigating the relationship between perfectionism and burnout. Moreover, the moderating effect of religious coping in this relationship was also investigated. The sample of the current study consisted of 210 physicians, with a reasonable mix of demographic characteristics, working in public and private health institutions in the greater Cairo Area. The data were obtained using a structured questionnaire to assess perfectionistic striving, perfectionistic concerns, religious coping and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Various studies in the literature support that religion is associated with being happier and more satisfied at work. There are also studies examining whether religiosity has a mediating or moderating effect with different variables such as burnout, job satisfaction, job stress, leadership, life satisfaction, and organizational commitment (Jamal and Badawi, 1993;Badawy and Mohamad, 2015;Ayten and Yıldız, 2016; and Sobol-Kwapinska, 2018;Safara et al, 2020;Vu, 2020;Abdul et al, 2021). Although there are studies in the literature investigating the relationship between burnout and religiosity, and between job satisfaction and religiosity, there are no studies investigating the moderating effect of religiosity on the relationship between these two variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies in the literature support that religion is associated with being happier and more satisfied at work. There are also studies examining whether religiosity has a mediating or moderating effect with different variables such as burnout, job satisfaction, job stress, leadership, life satisfaction, and organizational commitment (Jamal and Badawi, 1993;Badawy and Mohamad, 2015;Ayten and Yıldız, 2016; and Sobol-Kwapinska, 2018;Safara et al, 2020;Vu, 2020;Abdul et al, 2021). Although there are studies in the literature investigating the relationship between burnout and religiosity, and between job satisfaction and religiosity, there are no studies investigating the moderating effect of religiosity on the relationship between these two variables.…”
Section: Discussionmentioning
confidence: 99%
“…Jamal and Badawi (1993) revealed that religiosity moderated the relationship between job stressors and job motivation, job satisfaction, and organizational commitment. Badawy and Mohamad (2015) explored the moderating effect of religious coping on the relationship between perfectionism and burnout. Ayten and Yıldız (2016) examined the relationship between religiosity, religious coping, and life satisfaction in a sample of retired people.…”
Section: Moderating Effect Of Religiositymentioning
confidence: 99%
“…The working nature in a university involves many tasks as to deal with the students, colleagues, authority and the organization which demand a high level of communication skills and patience. Religiosity can handle negative emotions and employees with high religiosity tend to have a peaceful mind (Mohamad & Badawy, 2015;Zahid, 2017). A study conducted by Ho et al (2016) and Rose (2019) found that prayers, meditation, and similar rituals can help in reducing burnout and managing distress.…”
Section: Introductionmentioning
confidence: 99%